1996
DOI: 10.1007/bf02347615
|View full text |Cite
|
Sign up to set email alerts
|

Osteodystrophy in patients with chronic hepatitis and liver cirrhosis

Abstract: Bone mineral density (BMD) of the lumber vertebrae and factors related to bone metabolism were determined in patients with chronic viral hepatitis and patients with liver cirrhosis to clarify correlations between hepatic dysfunction, considered to be one of the causes of hepatic osteodystrophy, and decrease in bone mass. BMD of the second to fourth lumbar vertebrae was determined with a Lunar (Madison, WI, USA) DPX, a dual-energy X-ray absorptiometry diagnostic system. BMD was significantly lowest in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 20 publications
4
47
2
3
Order By: Relevance
“…Hypogonadism, abnormalities of vitamin D metabolism, and increased bilirubin levels, situations usually found in chronic liver disease, may lead to either reduced bone formation or increased bone resorption [23][24][25]. The results from the studies that have investigated the impact of hepatitis C on osteoporosis of hemophilia patients are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism, abnormalities of vitamin D metabolism, and increased bilirubin levels, situations usually found in chronic liver disease, may lead to either reduced bone formation or increased bone resorption [23][24][25]. The results from the studies that have investigated the impact of hepatitis C on osteoporosis of hemophilia patients are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal absorption of cholecalciferol (vitamin D3) and 25-hydroxycholecalciferol is affected only in the presence of severe cholestasis. Experimental studies have demonstrated that hepatic 25-hydroxylation of vitamin D3 is not impaired in cirrhotic rats, however, there is no evidence in humans [2].…”
Section: Introductionmentioning
confidence: 97%
“…Vitamin D is hydroxylated by liver to 25-hydroxy vitamin D, the main circulating form, and then is converted into the active form 1, 25-dihydroxyvitamin D in kidney [1,2]. Given that liver is involved in bile salt production, absorption of vitamin D, and 25-hydroxylation of vitamin D, it might be expected that vitamin D deficiency would be common in patients with chronic liver disease (CLD) [2].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In a study performed by Tsuneoka et al in 1993Tsuneoka et al in -1994 non-cirrhotic subjects with chronic viral hepatitis due to HBV (n=8) and HCV (n=12) were compared for bone metabolism with cirrhotic patients and also with age-sex matched healthy volunteers. 9 BMD was significantly decreased in patients with liver cirrhosis and, to a lesser extent, in patients with chronic hepatitis, compared with healthy subjects. In another study, Schiefke et al investigated BMD and bone turnover markers in biopsy-proven non-cirrhotic 43 patients (30 with HCV and 13 with HBV) with viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Osteodystrophy in patients with liver cirrhosis secondary to viral hepatitis has been well defined; however, there is little information about occurrence of bone disease in non-cirrhotic patients with chronic viral hepatitis, especially in asymptomatic hematite B virus (HBV) carriers. [9][10][11][12][13] Therefore, the aim of this study was to evaluate the bone mineral density (BMD) and the biochemical markers relevant the bone turnover in non-cirrhotic patients with chronic viral hepatitis B.…”
mentioning
confidence: 99%